Root Herbivory: Grass Species, Epichloë Endophytes and Moisture Status Make a Difference - Popay, Alison J. (Microorganisms, 2020)
The root-feeding scarab insect Costelytra giveni causes severe damage to pasture ecosystems in New Zealand. Loline alkaloids produced by some Epichloë endophytes deter this insect. In two experiments, tall fescue infected with E. coenophiala, strain AR584, and endophyte-free (Nil) controls were subjected to pulse drought stress (DS) or well-watered conditions (WW). The second experiment also included meadow fescue infected with E. uncinata. After 4–6 weeks exposure to the different conditions, roots were excised and fed to C. giveni larvae for 7 days. Relative root consumption (RC), frass production, and relative weight change (RWC) of larvae were measured and the loline content of roots determined. RC and frass output were higher for larvae feeding on Nil DS tall fescue than WW and reduced by AR584. RWC was also greater on DS than on WW Nil plants but reduced by endophyte only in DS plants. RC, frass output, and RWC of larvae were reduced by endophyte in DS and WW meadow fescue, but the effect was greater for WW plants. Loline alkaloid concentration in roots was significantly higher in DS than WW tall fescue in Experiment I but higher in WW than DS meadow fescue in Experiment II. These experiments have demonstrated that moisture status interacts with endophyte to differentially affect root herbivory in tall fescue and meadow fescue.